Fault Diagnosis Knowledge Reasoning of Switching Network in Distributed Generation Based on Petri Net - Liu, Ziquan; Zhu, Xueqiong; Ma, Jingtan; Hui Fu, Hui; Zhao, Ke; Hu, Chengbo (Distributed Generation & Alternative Energy Journal, 2021)
Telephone network based on IMS technology has been widely applied in power production and dispatching communication, especially in distributed power stations. Analysis and positioning failure of IMS network is arduous, because it’s dependent on IP data communication network. In this paper, we first introduced IMS switching network architecture and distributed gen- eration communication network architecture, analyzed and summarized all kinds of network malfunction. Combining typical IMS network fault con- nection relations, we introduced an improved Petri net fault handling model and reasoning method. The diagnosis and positioning results could reflect the defects of equipment logic functions. This method on fault diagnosis and location of substation network has been proved to be effective through practical application.